2021
DOI: 10.3390/su132212917
|View full text |Cite
|
Sign up to set email alerts
|

Green Credit Financing Equilibrium under Government Subsidy and Supply Uncertainty

Abstract: In this paper, we study the green credit financing equilibrium in a green supply chain (GSC) with government subsidy and supply uncertainty. The GSC system is composed of one manufacturer, two retailers, one bank, and the government. The manufacturer is subject to both supply uncertainty and limited capital. The manufacturer invests in the R&D of green products and borrows loans from the bank. The government subsidizes banks to encourage banks to provide loans to manufacturers with lower interest rates, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Government regulation can incentivize supply chain participants to choose green product development, promote overall government benefits, and achieve sustainable development for multiple stakeholders. Wu and Shang [33] constructed a green supply chain system consisting of manufacturers, retailers, banks, and the government, and studied the equilibrium of green credit financing under horizontal competition and cooperation through Stackelberg game models and numerical analysis. They examined how government subsidies and supply uncertainty affect green credit financing decisions.…”
Section: Government Regulation and Green Supply Chain Financementioning
confidence: 99%
“…Government regulation can incentivize supply chain participants to choose green product development, promote overall government benefits, and achieve sustainable development for multiple stakeholders. Wu and Shang [33] constructed a green supply chain system consisting of manufacturers, retailers, banks, and the government, and studied the equilibrium of green credit financing under horizontal competition and cooperation through Stackelberg game models and numerical analysis. They examined how government subsidies and supply uncertainty affect green credit financing decisions.…”
Section: Government Regulation and Green Supply Chain Financementioning
confidence: 99%
“…In the process of economic transformation, government subsidies are regarded as the most direct and easily observed mode of action of the "supporting hand" of the government. As free funds transferred by local governments to enterprises, government subsidies can encourage enterprises to increase green innovation input, directly enhance corporate earnings, and improve corporate financial constraints, thus easing the negative impact of GCP implementation on the financing of enterprises with high levels of pollution and energy consumption (Wu and Shang, 2021). The introduction of the GCP may make it difficult for enterprises with high levels of pollution and energy consumption to cross the capital threshold.…”
Section: The Moderating Effect Of Government Subsidiesmentioning
confidence: 99%
“…The effectiveness of government subsidies is another major research hotspot in academia, which has not reached a consensus due to different research objects, definitions of variables, and research methods. Some scholars believe that government subsidies bring positive signals, alleviate the pressure of external financing, stimulate enthusiasm for enterprise technology research and development, boost the innovation output of enterprises, and guide the direction of industrial development [18][19][20][21]; more innovation output wins market power for enterprises, significantly improves their profitability, and thus enhances their financial performance [22]. Some scholars have also found that government subsidies may cause some problems, such as rent-seeking behavior caused by enterprises taking advantage of information asymmetry or abuse of government subsidies [23].…”
Section: Motivation and Effectiveness Of Government Subsidiesmentioning
confidence: 99%